The Inner Life of Animals: Surprising Observations of a Hidden World - Peter Wohlleben (The Bodley Head, 2017)
Mother deer that grieve? Horses that feel shame? Squirrels that adopt their grandchildren? We humans tend to assume that we are the only living things able to experience feelings intensely and consciously. But have you ever wondered what's going on in an animal's head? From the leafy forest floor to the inside of a bee hive, The Inner Life of Animals takes us microscopic levels of observation to the big philosophical, ethical and scientific questions. We hear the stories of a grateful humpback whale, of a hedgehog who has nightmares, and of a magpie who commits adultery; we meet bees that plan for the future, pigs who learn their own names and crows that go tobogganing for fun. And at last we find out why wasps exist. As more and more researchers are discovering, animals experience a rich emotional life that is ready to be explored. The Inner Life of Animals will show you these living things in a new light and will open up the animal kingdom like never before.